2017
DOI: 10.1016/j.conctc.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale for a technology-based healthy lifestyle intervention in older adults grieving the loss of a spouse

Abstract: Introduction Experiencing the death of a spouse during late life is associated with an increased risk of developing debilitating mental health problems. Healthy lifestyle practices, such as regular exercise, healthy eating, and good sleep hygiene are promising strategies to influence the mental health and associated physical symptoms of late-life spousal bereavement. Objective This paper describes the design and rationale of an intervention development study addressing selective and indicated prevention of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…With regard to the motivations and advantages of using a mobile application, the results agree with the findings of Lau et al [22], who reported that the majority of women participating in their study expressed the practicality and ease of access anytime and anywhere, according to their status and their roles, the recommendation of friendly activities adapted to their needs and expectations as the main advantages of using mobile applications [23]. Stahl et al [24] showed that mobile applications are an option for the achievement of healthy lifestyles at all ages.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to the motivations and advantages of using a mobile application, the results agree with the findings of Lau et al [22], who reported that the majority of women participating in their study expressed the practicality and ease of access anytime and anywhere, according to their status and their roles, the recommendation of friendly activities adapted to their needs and expectations as the main advantages of using mobile applications [23]. Stahl et al [24] showed that mobile applications are an option for the achievement of healthy lifestyles at all ages.…”
Section: Discussionsupporting
confidence: 88%
“…We assume that adapting to the process of senility may enable the caregiver to be calm at the time of death and provide appropriate end-of-life care sufficiently. Although aging and senility are laws of nature and death is unavoidable, caregivers often find it difficult to put aside their expectations and frequently experience significant emotional upheaval [30]. The six items that comprised this first factor, such as “acceptance of death,” “acceptance of senility,” and “development of a system for the moment of death,” highlighted the importance of slowly and gradually accepting and adapting to senility and death, even when experiencing anxiety at the passing of a loved one disturbs one’s emotional stability.…”
Section: Discussionmentioning
confidence: 99%
“…The app also provided feedback in real time about participants' sleep, meals, and physical activity (see Stahl et al, 2017 for design and pilot testing of app). 9 Participants randomized to DM + coach received weekly calls from a health coach who used motivational interviewing (MI) techniques to strengthen participants' intrinsic motivation to engage in a regular behavioral routine. Using the MI Treatment Integrity Coding Manual -four components of MI were met during each session: open-ended questions, affirmations, reflective listening, and summarizing statements.…”
Section: Interventionsmentioning
confidence: 99%